Myelodysplastic syndrome with t(9;22)(p24;q11.2), a BCR-JAK2 fusion: case report and review of the literature - TOPTAŞ, TAYFUR (SPRINGER JAPAN KK, 2015)
The human JAK2 gene is mainly targeted by two types of genetic lesions that play roles in the pathogenesis of hematologic malignancies: intragenic mutations and chromosomal translocations. Chromosomal translocations of JAK2 are typically associated with myeloid or lymphoid malignancies with an aggressive course and poor outcome. Here we report a t(9;22)(p24;q11.2) translocation, in a MDS patient and review results associated with BCR-JAK2 fusion reported in the literature.
Keywords: t(9;22); Myelodysplastic syndrome; BCR-JAK2; Fusion gene; JAK2 rearrangement; CHRONIC EOSINOPHILIC LEUKEMIA; ACUTE LYMPHOBLASTIC-LEUKEMIA; CHRONIC MYELOID-LEUKEMIA; JAK2; TRANSLOCATION; PATIENT; GENE; RUXOLITINIB; REARRANGEMENTS; DISORDERS